Slovensko slovaropisje in kritika - Merše, Majda (Slavia Centralis, 2020)
SLOVENE LEXICOGRAPHY AND CRITIQUEA parallel phenomenon to Slovene lexicography has been its critique, which has been brought to the fore only in the past two centuries. Lexicographic works of a general nature received the most signifcant critical response, i. e., the Slovar slovenskega knjižnega jezika [Dictionaryof Standard Slovene] (1970–1991) and Slovenski pravopis [Slovene Orthography] (2001). The article presents the scope of lexicographic critique, its typology and impact, as well as the main critical issues, along with some sample material.
Keywords: Slovene language; lexicography; lexicographic typology,; critique